Understanding organisational risks and opportunities associated with implementing Australia's national disability insurance scheme from the nonprofit service provider perspective: Findings from quantitative research - Hamin Hamin; David Rosenbaum; Elizabeth More (Journal of Risk and Financial Management, 2022)
In this paper, we provide useful lessons from a quantitative analysis across several nonprofit organisations undergoing generational change due to the implementation of the Australian government's National Disability Insurance Scheme (NDIS). This paper contributes to the field in demonstrating the usefulness of the approach in revealing how change has to occur at both the micro and macro levels of the organisations involved, affecting both followers and transforming leadership, whilst simultaneously reinforcing the need to address the strategic and operational risks inherent in such transformational change. It represents a follow-up to an earlier published longitudinal qualitative research and provides further evidence on the key findings associated with the development of the NDIS Implementation Framework. The current paper considers the importance of the risk and opportunity conundrum associated with the implementation of the NDIS among Australian nonprofit service providers. This paper recognises that, as entities operating ostensibly outside the purely commercial realms of service design and delivery, nonprofit service providers are potentially handicapped by an historic lack of relevant and necessary market-based skills. The risks necessitate an accelerated programme of skill development and skill acquisition to enable the full range of opportunities to be realised. The change management processes, identified using the conceptual framework of readiness Ç implementation commitment Ç sustainability, as discussed in this paper, highlight the potential financial consequences which have substantial impacts on such nonprofit service providers. Organisations in these settings are challenged by ongoing financial sustainability issues where very small financial margins, resulting directly from the generational business model shift from a supply-driven system to a demand-driven system, may prove the difference between organisational survival and failure.
Keywords: 650; financial risk; sustainability; business models; NDIS Implementation Framework; nonprofits; transformational change